Fast Raman spectral mapping of highly fluorescing samples by time-gated spectral multiplexed detection - Corden, Christopher; Shipp, Dustin; Matousek, Pavel; Notingher, Ioan (Christopher Corden, 2018)
We present a time-gated Raman micro-spectroscopy technique suitable for fast Raman mapping of samples eliciting large laser-induced fluorescence backgrounds. To achieve the required time resolution for effective fluorescence rejection, a picosecond pulsed laser and a single-photon avalanche diode were used. A module consisting of a spectrometer, digital micromirror device, and two prisms was used for high-resolution spectral filtering and multiplexing, which is required for a high chemical specificity and short integration times. With this instrument, we demonstrated time-gated Raman imaging of highly fluorescent samples, achieving acquisition times as short as 3 min for 40×40 pixel resolution images.